2006
DOI: 10.1139/h06-007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise and nutritional counseling in women with polycystic ovary syndrome

Abstract: This pilot study assessed the effects of exercise and nutritional counseling on hormonal, menstrual, and reproductive function in women with polycystic ovary syndrome (PCOS). Twelve females with a clinical, biochemical, and ultrasonographic diagnosis of PCOS were randomly assigned to endurance and resistance exercise plus nutritional counseling (EN) or nutritional counseling only (N) for a period of 12 weeks. Anthropometry, resting metabolic rate (RMR), selected hormones, and ovarian follicle population were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 61 publications
3
135
0
2
Order By: Relevance
“…Chronic exercise training increases RMR and is therefore always recommended as an adjunct to any caloric restriction . A pilot study conducted by Bruner et al (2006) has shown that a combination of exercise and nutritional counselling in women with PCOS, as well as nutritional counselling alone, had favourable effects on waist girth, body fatness and fasting insulin levels, as well as a trend towards an increase in RMR in the exercise and nutrition group after completion of the intervention (Bruner et al, 2006). Recent studies investigating the effects of exercise in women with PCOS also showed that a 3-months structured exercise training programme caused significant improvement in cardiopulmonary functional capacity, decreased BMI, improved insulin sensitivity (Vigorito et al, 2007) and after 6-months even restored ovulation (Palomba et al, 2008).…”
Section: Non-pharmacological Management Of Obesity In Pcos Patientsmentioning
confidence: 99%
“…Chronic exercise training increases RMR and is therefore always recommended as an adjunct to any caloric restriction . A pilot study conducted by Bruner et al (2006) has shown that a combination of exercise and nutritional counselling in women with PCOS, as well as nutritional counselling alone, had favourable effects on waist girth, body fatness and fasting insulin levels, as well as a trend towards an increase in RMR in the exercise and nutrition group after completion of the intervention (Bruner et al, 2006). Recent studies investigating the effects of exercise in women with PCOS also showed that a 3-months structured exercise training programme caused significant improvement in cardiopulmonary functional capacity, decreased BMI, improved insulin sensitivity (Vigorito et al, 2007) and after 6-months even restored ovulation (Palomba et al, 2008).…”
Section: Non-pharmacological Management Of Obesity In Pcos Patientsmentioning
confidence: 99%
“…In such cases, WC was approximated at the lateral level of the 12 th rib or lower floating rib. [23][24][25][26] These are well established and validated methods for assessment of hip circumference and WC and are used in several large scale studies. 27 Bioelectrical impedance was done using the Quantum II Bioelectrical Body Composition Analyzer (RJL Systems, Clinton Township, MI).…”
Section: Measurement Of Body Fat and Fat Distribution Indicesmentioning
confidence: 99%
“…Lifestyle modification should include nutrition counseling as well as an exercise program. Nutrition counseling alone has demonstrated a decrease in weight gain and body fat as well as lowering insulin levels (Bruner, Chad, & Chzen, 2006).…”
Section: Intervention and Treatment Optionsmentioning
confidence: 99%
“…Decreasing body fat, especially within the abdomen may also improve metabolic and hormonal profiles even with only a minimal loss in overall body mass (Bruner et al, 2006). social, and emotional challenges on a daily basis.…”
Section: Intervention and Treatment Optionsmentioning
confidence: 99%